Harlequin Ichthyosis: Case Series - Huriye Ezveci; Sukran Dogru; Fatih Akkus; Kazim Gezginc (Gynecology Obstetrics & Reproductive Medicine)
Objective: Harlequin ichthyosis (HI) is an autosomal-recessive inherited disorder. The incidence is extremely rare and is reported to range from 1/300 000 to 1/1 000 000. Some risk factors include preterm births and consanguinity. Prenatal DNA testing for the ABCA12 mutation aids in diagnosis. Although ultrasonography helps the diagnosis, the diagnostic value of a single ultrasound is low. It is fatal for the affected newborn after the first few days after birth, but few long-term survivals have been recorded. The hallmark of with disease is severely keratinized skin. This study aims to evaluate the prenatal and postnatal outcomes of cases with HI.